Analisis Tindak Tutur Ilokusi dalam Video Cerita Rakyat pada Kanal Youtube Dongeng Kita - Nur Jihan Iklimah; Fora Shaffilia Hakiki; Diva Fajria Rahma; Amanda Ivani; Asep Purwo Yudi Utomo; Antonius Edi Nugroho; Annisa Tetty Maharani (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Speech acts are one of the objects of pragmatic study which relate human behavior to the means of speech. There are three types of speech acts in pragmatics, namely illocutionary, locutionary, and perlocutionary. Illocutionary acts as a type of speech act function to say and carry out an action, which is divided into representative, directive, expressive, commissive, and declarative speech acts. This research aims to examine and describe words, phrases, clauses, or sentences containing illocutionary speech acts in folklore videos on the Dongeng Kita YouTube channel, each of which has the title “Cerita Rakyat Sumatera Barat (Malin Kundang)”, “Cerita Rakyat Sumatera Barat (Legenda Dayang Bandir dan Sandean Raja)”, “Cerita Rakyat Jambi (Negeri Lumpur)”, “Cerita Rakyat Jambi (Dusun Selat)”, dan “Cerita Rakyat Bangka Belitung (Asal Mula Pulau Kapal)”. The research method applied is a qualitative descriptive method with free-involved listening techniques followed by note-taking techniques. The results of the analysis carried out were that there were 66 utterances including illocutionary speech acts, which were classified into 17 representative speech acts, 21 directive speech acts, 19 expressive speech acts, 5 commissive speech acts, and 4 declaration speech acts. This research has broad benefits for understanding communication, language analysis, developing communication skills, and contributing to communication theory and related scientific disciplines.